Application of QRIS as Digital Payment in The Tourism Industry During A Pandemic: A Focus Group Discussion (Case Study of Alun-Alun Kidul Yogyakarta) - Bhinadi, Ardito; Kaswidjanti, Wilis; Negara, Hari Kusuma Satria; Mastrisiswadi, Hasan (RSF Conference Series: Business, Management and Social Sciences, 2021)
The pandemic has changed people's habits or people's behavior in non-cash transactions using digital wallets or e-wallets to reduce the risk of being infected with the coronavirus, one of which is by using QRIS. However, we have not often encountered the use of digital payment technology through QRIS in tourism locations. One of them is the South Square of Yogyakarta. This research is qualitative research using the Focus group discussion method. In this study, the number of participants in this FGD was ten people from the team, ISEI, and tourism industry players in Alun-Alun Kidul Yogyakarta. Based on the results of the research that has been done, the first conclusion is that the use of QRIS in Alun-Alun Kidul Yogyakarta is still minimal, even though 80% have received the code, but only 30% have activated it, and who use it no more than 2%. Some several obstacles and challenges cause this, including the low number of visitors, regulations that are not required, and the mindset of traders who still use traditional financial management systems. The alternative solution offered is QRIS activation for tourism industry players who have not yet performed and provided mobile services from BPD.